(untitled) (London, 2009)
The approach known as Integrated Water Resources Management (IWRM) is widely recognized as the best way forward, but is poorly understood, even within the water sector. Through case studies, from both developed and developing countries on five continents, this book illustrates how better water management, guided by the IWRM approach, has helped to meet a wide range of sustainable development goals. It does this by considering practical examples, looking at how IWRM has contributed, at different scales, from very local, village level experiences to reforms at national level and beyond to cases involving trans-boundary river basins. Using these on-the-ground experiences, the book provides candid and practical lessons for policy makers, donors, and water and development practitioners worldwide looking at how IWRM principles were applied, what worked, and, equally important, what didn't work, and why.
Keywords: Water-supply,Water resources development,Sustainable development,Cung cấp nước,Phát triển nguồn nước,Phát triển bền vững; Management,Quản lý